2016
DOI: 10.14796/jwmm.c409
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Transient Pneumatic Events in a Combined Sewer Overflow Storage Tunnel System

Abstract: The City of Portland, Oregon recently completed construction of the Willamette combined sewer overflow tunnel system to contain combined sewage during storm events and prevent unauthorized release of sewage to the Willamette River. The system includes a network of consolidation conduits designed to intercept combined flows and convey them to tunnel drop shafts. After bringing the system online, the effects of pressure surges were observed at various locations along the conduits and interceptor sewers, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Clearly, if the manhole cover is bolted to the shaft, the bolts will maintain the cover in position and so transfer the air pressure forces to the supporting ring. As would be expected, structural damage can occur if these forces are excessive, as was reported by Klaver et al (2016). Assuming that the air pressure under a poorly ventilated manhole cover with an area of 0.5 m 2 reached the same range that was obtained in these simulations, the air pressure force could reach 48.7 kN.…”
Section: Figure 5 Detail Of Air Pressure Variation Under a Manhole Cosupporting
confidence: 79%
See 1 more Smart Citation
“…Clearly, if the manhole cover is bolted to the shaft, the bolts will maintain the cover in position and so transfer the air pressure forces to the supporting ring. As would be expected, structural damage can occur if these forces are excessive, as was reported by Klaver et al (2016). Assuming that the air pressure under a poorly ventilated manhole cover with an area of 0.5 m 2 reached the same range that was obtained in these simulations, the air pressure force could reach 48.7 kN.…”
Section: Figure 5 Detail Of Air Pressure Variation Under a Manhole Cosupporting
confidence: 79%
“…For the largest non-extreme value of A * v that we considered (A * v = 0.1), the peak pressure head was 1.0 m. The results show that in general air pocket releases can cause a large air pressure under a manhole cover. For comparison, the peak air phase pressure heads reported by Klaver et al (2016) were <1.7 m for cases when manholes were subjected to inertial oscillations during rapid filling conditions and for a ventilation area of A * v = 0.0017. After air pressure peaked, there was a process of depressurization due to ventilation in all cases except for the case when A * v = 0.…”
Section: Figure 5 Detail Of Air Pressure Variation Under a Manhole Comentioning
confidence: 99%
“…Later work by Wright (2013), Vasconcelos and Leite (2012) and Lewis (2011) extended our understanding of the role of air in the pressurization of rapidly filling storm water systems. Klaver et al (2016) used a numerical model for rapid filling that included air pressurization effects and, following a wet weather event in Portland, Oregon, they concluded that pressurized air in a sealed access point riser was responsible for damage to the riser structure and the surrounding asphalt pavement. Based on this work, a similar approach was adopted to assess the extent to which air pressurization was responsible for the current problem.…”
Section: Problem Statementmentioning
confidence: 99%
“…Table 1 provides the maximum total inflow rate to the Alder shaft for each event, as well as two WSEs at the shaft: one representing the level at the time of the peak inflows, and the other representing the maximum level from the entire event. Table 1 also includes an event from 2013-09-28 for comparison; this event, which flooded the consolidation sewers but did not flood to grade, was previously investigated as part of a study investigating pneumatic issues (Klaver et al 2016). The September and October events had similar maximum inflow rates, but for the September event this peak was reached while the WSE in the tunnel was well below grade; in the October event, on the other hand, the WSE concurrent with the peak inflow was high enough to submerge the Alder shaft vortex drop structure.…”
Section: Observed Eventsmentioning
confidence: 99%
“…(0.076 m). The model was also run using boundary conditions from the 2013-09-28 event, which was previously modeled in the transient pneumatic study (Klaver et al 2016); no flooding was documented during this event, and the test SWMM application did not predict flooding either.…”
Section: Rating Curve Development For Stark Vortex Drop Structurementioning
confidence: 99%